From a Shapiro–Keyser extratropical cyclone to the subtropical cyclone Raoni: An unusual winter synoptic situation over the South Atlantic Ocean - Reboita, Michelle Simões; Gozzo, Luiz Felippe [UNESP]; Crespo, Natália Machado; Custodio, Maria de Souza [UNESP]; Lucyrio, Vinícius; Jesus, Eduardo Marcos de; Rocha, Rosmeri Porfírio da (Wiley, 2022)
The eastern coast of South America is a cyclogenetic region in terms of extratropical cyclones and, in lower number, of subtropical cyclones that are more frequent in austral summer and autumn. However, in June 2021, an unusual cyclone developed near the boundary of Uruguay and southern Brazil, initially having extratropical features and later undergoing a subtropical transition. At 1200 UTC 29 June, the Brazilian Navy named it as subtropical cyclone Raoni. This study aims to describe the synoptic evolution of the cyclone and address physical drivers for the subtropical transition based on the ECMWF-ERA5 reanalysis and numerical experiments with the WRF model. The cyclone precursor of Raoni had its genesis at 1800 UTC 26 June 2021 forced by a trough at mid–upper levels that crossed the Andes Mountains and caused a rapid surface pressure drop. Less than 24 hr later, the cyclone presented a frontal T-bone pattern and warm seclusion, following the Shapiro–Keyser development model. Strong surface heat fluxes, a deep moist troposphere, and the vertical alignment of the warm seclusion with an upper-level cut-off pattern provided the adequate environment for organising convection and, consequently, for subtropical transition at 0600 UTC 28 June. The fundamental role of the surface turbulent heat fluxes for the transition is confirmed through numerical experiments. This study is unprecedented in the sense that no subtropical cyclone originating from a warm seclusion has been documented over the South Atlantic before. These findings emphasise the need of monitoring cold-season extratropical Shapiro–Keyser cyclones in the region since they can evolve to a subtropical or tropical cyclone and can cause damage to the maritime activities and coastal region due to the strong winds.
Keywords: cyclone phases; numerical experiments; South Atlantic Ocean; subtropical cyclone; synoptic evolution; warm seclusion